A Novel Conformal MIMO Antenna Array based a Cylindrical Configuration for 5G Applications - Al-Tameemi A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
The proposed antenna array is developed based on four printed monopole antennas for multi input multi output (MIMO) 5G systems at Sub-6 GHz bands. The antenna design is structured from Moore fractal geometry connected to T-stub structure. The main objective of introducing the Moore fractal is to improve the antenna bandwidth through accumulating the electric charges in the air gap between the T-stub and the proposed fractal. Therefore, the resulted antenna when excited with a coplanar waveguide (CPW) shows several operating bands at 2.3GHz, 4GHz, 4.7GHz, and 5.4GHz. The generated modes are attributed to the use of the proposed fractal in which the radiation properties of the antenna are almost broadside radiations over the frequency bands of interest. The antenna array is folded on a cylindrical substrate with a radius of 15mm and hight of 34mm of 1mm thickness. The proposed antenna performance is optimized parametrically using CST software packages. Therefore, the proposed antenna design is developed to constructed the array for MIMO applications. The proposed array is oriented on a cylindrical substrate with a separation distance below ?/21, where, the separation measured in terms of the closes gab between adjacent patches edges. The antenna array is found to show a bandwidth from 5GHz to 5.9GHz is achieved with S11 below-10dB. The proposed antenna array shows a coupling effect below-10 dB. The antenna shows a gain of 2.5dBi at 5.4GHz. Nevertheless, the antenna gains at 2.3GHz, 4GHz, and 4.7GHz are found to be 4.2dBi, 1dBi, and 3.5dBi. Finally, it is found that the proposed antenna array shows high diversity with a minimum correlation factor. 2022 Institute of Advanced Engineering and Science (IAES).